Respuesta :

Answer:

9.2

Step-by-step explanation:

8x^2-18x-5

64x-18x-5

46x=5

9.2

mark brainliest please

Answer:

(4x + 1)(2x - 5)

Step-by-step explanation:

To factor 8x² - 18x - 5

Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 8 × - 5 = - 40, sum = - 18

The factors are + 2 and - 20

Use these factors to split the x- term, that is

8x² + 2x - 20x - 5 ( factor the first/second and third/fourth terms )

= 2x(4x + 1) - 5(4x + 1) ← factor out (4x + 1)

= (4x + 1)(2x - 5) ← in factored form